Perspectives on lecithin from egg yolk: Extraction, physicochemical properties, modification, and applications - Zhao, Feng; Li, Rongji; Liu, Yun; Chen, Haiyan (Frontiers in Nutrition, 2023)
The molecular structure, extraction method and functional activity of egg yolk lecithin are reviewed, and the latest research status of lecithin in medical treatment is introduced. At present, the methods for extracting egg yolk lecithin mainly include solvent extraction and supercritical extraction; egg yolk lecithin has physiological activities such as antioxidant, antibacterial, anti-inflammatory, neuroprotection, and cardiovascular and cerebrovascular protection; in addition, it is summarized through literature search. The application status of egg yolk lecithin liposomes at home and abroad are reviewed. It provides a good reference for the development of egg yolk lecithin products.It provides some references for the study of biological modification and metabolism of egg yolk lecithin in China in the future.